Education on Sorting and Management of Organic and Inorganic Waste in Dusun IV, Batukarut Village, Bandung Regency - Mastiani, Emay; Firdaus, Ahmad Hilmi; Wildan A K, Muhammad; Farhan, Cecep Muhammad; Hermansyah, Deden; Rizmawan, Rizal; Zhafir, Hasna Aulia; Suganda, Shalsa Nabila; Ningsih, Reni Priatna; Abdurahimi, Sani Ramdan; Disastra, Tesa Adipuri; Agfinita, Yuniar; Lavision, Zavira Aina (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Waste is a serious problem that is often faced in today's society. This Community Service Activity was carried out in Hamlet IV, Batukarut Village, Bandung Regency. Community knowledge in Hamlet IV, Batukarut Village about waste and its management is still minimal. Supporting facilities do not help this condition. Therefore, it is important to raise awareness among residents not to litter and educate them on how to sort waste. Starting from this problem, this community service activity aims to provide a solution through education on the importance of maintaining cleanliness, selecting and differentiating organic and inorganic waste and utilizing waste food so that it has economic value. The real form of this activity is in the form of assistance in providing segregated waste bin facilities. The method used in implementing this service activity is education through seminar, licensing, preparation, implementation and evaluation stages. The results of this community service activity are awareness of the importance of maintaining cleanliness, increased understanding of independent waste sorting and knowledge of its benefits. Apart from that, the people of Pecalongan can also find out the benefits of processing waste using the 3R method, namely: Reduce, Reuse, Recycle